Continuous versus punctuated vein widening in the Marcellus Formation, USA: the fine line between pressure fringes and hydraulic fractures - Hooker, JN; Cartwright, J; Stephenson, B; Day, C (Cambridge University Press, 2022)
Calcite veins are common in organic-rich mudrocks, but their genesis and ability to transmit fluids are debated. A combined microstructural and isotopic investigation of an array of calcite veins recovered in core from the Marcellus Formation reveals that the veins grew via a combination of continuous fibrous growth and punctuated fracture-opening increments. Continuous opening is the result of pressure-solution creep and involves no mechanical fracturing, but rather the growth of a pressure fringe around a pre-existing, sealed fracture. In contrast, incremental opening is accomplished by overpressured, mineral-saturated fluid, which repeatedly ruptures the rock at the cement / host-rock interface. Punctuated growth increments occurred repeatedly throughout an otherwise protracted, continuous growth history, indicating that the present structures preserve hybrid deformation conditions between brittle, fluid-assisted cracking and plastic strain. Stable isotopic signatures match those of a regional opening-mode fracture set that formed in response to catagenetic fluid overpressures amid a tectonically imposed (Alleghanian) stress field. It is concluded that calcite veins form as opening-mode hydraulic fractures and are susceptible to increments of brittle reactivation, even while inelastic growth processes widen and fill the veins with fibrous cement.